Beauty Influencers and Instagram Usage - Lopez, Jace; Islam, Sayeedul (Journal of Applied Business and Economics, 2021)
Instagram has become a popular platform for beauty influencers. It’s a versatile and user-friendly platform. Beauty influencers use their profiles in a variety of ways that can impact social media users. Social media users perceive social media influencers and their profiles in different ways, affecting engagement rate. 5 macro-influencers and 5 micro-influencers were used in this study. Researchers coded 285 Instagram posts according to the content type used. Follower counts, overall likes, and overall comments were collected. Instagram engagement rate was calculated for each post. Macro-influencers had a higher engagement rate than micro-influencers. Micro-influencers used more hashtags than macro-influencers. Both macroinfluencers and micro-influencers used entertaining content and brand information than relational content and field information.